2022
DOI: 10.19128/turje.841709
|View full text |Cite
|
Sign up to set email alerts
|

Öz düzenleyici öğrenme stratejileri ve öz yeterlik inancının İngilizce öğrenme başarısını yordamadaki rolü

Abstract: The self-regulation and self-efficacy beliefs have a major effect on English language learning achievement. This study examines if self-regulatory learning strategies and English self-efficacy beliefs significantly predicted learning achievement in learning English. 542 ninth grade students studying at ten different Vocational and Technical Anatolian High Schools formed the sample. Data were gathered through the Self-Regulatory Learning Strategies Scale, the English Self-Efficacy Beliefs Scale and the ninth gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…. and DiBenedetto, 2021; Zysberg and Schwabsky, 2021;Kontaş and Özcan, 2022;Muhtadi et al, 2022;Zorlu and Ünver, 2022;Luo et al, 2023;Salvo-Garrido et al, 2023;Al-khresheh and Alkursheh, 2024;Bozzato, 2024) and that BPN satisfaction predicts achievement (Taylor et al, 2014;Nalipay et al, 2020;Theis et al, 2020;Ahn et al, 2021;Buzzai et al, 2021;Afzal and Jami, 2023;Earl et al, 2023;Vijayakumaran et al, 2023;Wangchuk, 2023;Zhang and Jiang, 2023;Zupančič et al, 2024). The linkage between selfefficacy, BPN and achievement; however, has not yet been well established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…. and DiBenedetto, 2021; Zysberg and Schwabsky, 2021;Kontaş and Özcan, 2022;Muhtadi et al, 2022;Zorlu and Ünver, 2022;Luo et al, 2023;Salvo-Garrido et al, 2023;Al-khresheh and Alkursheh, 2024;Bozzato, 2024) and that BPN satisfaction predicts achievement (Taylor et al, 2014;Nalipay et al, 2020;Theis et al, 2020;Ahn et al, 2021;Buzzai et al, 2021;Afzal and Jami, 2023;Earl et al, 2023;Vijayakumaran et al, 2023;Wangchuk, 2023;Zhang and Jiang, 2023;Zupančič et al, 2024). The linkage between selfefficacy, BPN and achievement; however, has not yet been well established.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of several positively correlated agentic processes that are predictive of academic achievement (Code, 2020). Academic self-efficacy is associated with academic performance in reading literacy (Yang et al, 2018;Ocak and Tiraki, 2020;Zysberg and Schwabsky, 2021;Zorlu and Ünver, 2022), mathematics (Kitsantas et al, 2011;Xu and Qi, 2019;Ugwuanyi, 2020;Zysberg and Schwabsky, 2021;Er et al, 2022;Kontaş and Özcan, 2022;Muhtadi et al, 2022), and the sciences (Aurah, 2017;Oyelekan et al, 2019;Gao et al, 2020;Adjei et al, 2023;Dever, 2024) and is positively associated with overall academic achievement (Asakereh and Yousofi, 2018;Akturk and Ozturk, 2019;Olivier et al, 2019;Usher et al, 2019;Zysberg and Schwabsky, 2021;Luo et al, 2023;Salvo-Garrido et al, 2023;Al-khresheh and Alkursheh, 2024;Bozzato, 2024).…”
Section: Self-e Cacy and Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Vocational School a major proportion of the problems stem from student self-variables. There are insufficiencies in students' backgrounds (Liu, 2020;Muliyah & Aminatun, 2020;Sun Spencer, 2008;Wen, 2010), they have negative attitudes toward English instruction (Liu, 2020;Muliyah & Aminatun, 2020;Sun Spencer, 2008), and feel themselves inefficient (Zorlu & Ünver, 2022;Lovejoy, 1995, Wang, Chao, & Liao, 2011. The framework of the Self System Model of Motivational Development (SSMMD) permits us to understand the success of education in relation to students' motivational processes and interactions with their social context.…”
Section: Discussionmentioning
confidence: 99%
“…The self-regulation and self-efficacy beliefs have a major effect on English language learning achievement. Zorlu and Ünver (2022) found that 542 Vocational High School students' selfregulatory learning strategies and English self-efficacy beliefs significantly predicted learning achievement in learning English. While this is the case, undesirable start and emotional distress of students affect the Vocational School students' academic performance negatively (Lovejoy, 1995;Wang, Chao, & Liao, 2011).…”
Section: Background To the Studymentioning
confidence: 94%